Physiological Effect of Hematological Parameters From Exposure to Radiation of Mobile - Mohammed, Hassanein Fadel; Obaid, Sarah Abbas (Medical Science Journal for Advance Research, 2026)
Background: Today we live in a rapidly accelerating technological era, which is called by many names, including the era of the global technological revolution, the era of information technology, and the technological explosion. Methods: Fouty five samples were divided into three study groups: fifteen sample 15 uses phone for more than 2 hours daily, and fifteen sample 15 uses phone for more than 5 hours daily and fifteen sample 15 uses phone for less than 1 hours daily (control group) . The samples was collected from the in AL-Najaf province/ Iraq and during the period from October 2024 until January 2025. The age of sample from 17 to 40 years. All participants were exposed to questionnaire about age, number of use phones mobile , then blood samples was collected and sent for analysis. Both sample is informed about the study and consent was ensured . Results: the results show when 2 hours exposure to radiation from mobile phone on leukocytes counts significantly increased (p<0.001) in total leukocytes count in compared with control groups, while, no significantly differences in Lymphocytes (%), Neutrophils (%), Monocytes (%), Eosinophils (%) and Basophils (%) with control groups. the result show when 5 hours person exposure to radiation on total counts of leukocytes, significantly increased (p<0.001) in total leukocytes count and Lymphocytes (%) and decrease in Neutrophils (%) in compared with control groups, while, no significantly differences in Monocytes (%), Eosinophils (%) and Basophils (%) with control groups. Also the resulr show when 2 hours exposure to radiation from mobile phone on total red bloods , no significantly differences in Total RBCs count and Hb (g/dl) and PCV (%) , MCV (fL), MCH (pg) and MCHC (g/dl) in compared with control. Also the resulr show when 5 hours exposure to radiation from mobile phone on total red blood corpuscles and red blood cell absolute values , significantly increased (p<0.001) in Total RBCs count and Hb (g/dl) and PCV (%) in compared with control groups, while, no significantly differences in MCV (fL), MCH (pg) and MCHC (g/dl) with control groups. Conclusion: The current study indicated that Using a mobile phone for long period have effect on hematological parameters., The change that occur from long period of use of phone causes increase in count of WBC and lymphocyte also increase in RBC count and Hb and PCV.